(untitled) (Research, Society and Development, 2019)
The slogan is a communicational element widely used to delimit in a few words an ideal or an idea chosen to be in the memory of its targeted audience. In the case of candidates for the presidency of the republic, it is an important element of persuasion, while offering an opportunity to know, briefly, the purpose of the candidate to the top place of the Republic. The objective of this project was to study the slogans of elected presidents and the second placed in the dispute, in the New Republic elections, beginning in 1989. Through documentary research, bibliographical analysis and field research of the 166 interviewees, a comparison was made between the slogans of each election and analyze their power of persuasion on the electorate. The analysis concluded that compelling slogans do not necessarily guarantee the victory of their candidates, but misguided choices could be decisive in defeat in electoral lawsuits.